2019
DOI: 10.3389/fnhum.2019.00388
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation Optimization – From Physics-Based Computer Simulations to High-Fidelity Head Phantom Fabrication and Measurements

Abstract: BackgroundTranscranial direct current stimulation (tDCS) modulates neural networks. Computer simulations, while used to identify how currents behave within tissues of different conductivity properties, still need to be complemented by physical models.Objective/HypothesisTo better understand tDCS effects on biology-mimicking tissues by developing and testing the feasibility of a high-fidelity 3D head phantom model that has sensing capabilities at different compartmental levels.MethodsModels obtained from MRI im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…When using the bilateral dorsolateral prefrontal cortex (DLPFC) tDCS montage, the computer-simulated and phantom-measured voltages at the brain and skull layers were similar (except at excitation locations in the skull layer under the tDCS electrodes), and our gray matter electric field and potential distributions were consistent with previous computerized models. Furthermore, the circular tDCS electrodes led to greater electric field confinement in the different layers of the phantom compared to rectangular electrodes, as well as higher voltages at those layers [7].…”
Section: Phase I (Realistic Phantom Head Modeling)mentioning
confidence: 93%
See 2 more Smart Citations
“…When using the bilateral dorsolateral prefrontal cortex (DLPFC) tDCS montage, the computer-simulated and phantom-measured voltages at the brain and skull layers were similar (except at excitation locations in the skull layer under the tDCS electrodes), and our gray matter electric field and potential distributions were consistent with previous computerized models. Furthermore, the circular tDCS electrodes led to greater electric field confinement in the different layers of the phantom compared to rectangular electrodes, as well as higher voltages at those layers [7].…”
Section: Phase I (Realistic Phantom Head Modeling)mentioning
confidence: 93%
“…In Phase I of this study [7], we developed a 3D head phantom model based on an MRI image stack of a healthy person allowing us to estimate electric current diffusion in tissues of different conductivity. We embedded 18 EEG monitoring electrodes into the model at skull and gray matter tissue layers and compared electric voltage measurements in phantom and computerized models before and after tDCS using different montages: Montage 1 (rectangular electrodes, bilateral DLPFC), Montage 2 (circular electrodes, left primary motor cortex [M1]-right supraorbital) and Montage 3 (circular electrodes, bilateral M1) [7]. We confirmed feasibility of the high-fidelity 3D head phantom model and also found high correlation between computer-simulated and phantommeasured voltages, especially at the brain level.…”
Section: Phase I (Realistic Phantom Head Modeling)mentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments are only part of the verification of the abovementioned optimization methods, and there are many studies that have explored the method and effect of optimization through computer simulation to explain the mechanism of optimization methods. Different models were established to determine whether electrical stimulation was effective and to optimize the number of electrodes and electrode arrangement (Morales-Quezada et al, 2019 ). Aberra established a computational model of human and rat cortical neurons to simulate the neural response of the cerebral cortex stimulated by electromagnetic fields (Aberra et al, 2018 ).…”
Section: Computer Stimulationmentioning
confidence: 99%
“…Compared with the classical electrode montage, the ring electrode montage can stimulate the target region more intensively and significantly reduce neurosensory side effects (Heise et al, 2016 ). In addition, studies found that circular electrodes have a better restraining effect on the electric field distribution of different phantom layers than rectangular electrodes (Morales-Quezada et al, 2019 ).…”
Section: Computer Stimulationmentioning
confidence: 99%